2021
DOI: 10.1186/s10020-021-00342-y
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant N-acetylcysteine promotes immune response and inhibits epithelial-mesenchymal transition to alleviate pulmonary fibrosis in chronic obstructive pulmonary disease by suppressing the VWF/p38 MAPK axis

Abstract: Background/aim N-Acetylcysteine (NAC) demonstrates applications in the prevention of exacerbation of chronic obstructive pulmonary disease (COPD). COPD is often characterized by fibrosis of the small airways. This study aims at investigating the physiological mechanisms by which NAC might mediate the pulmonary fibrosis in COPD. Methods A total of 10 non-smokers without COPD and 10 smokers with COPD were recruited in this study, and COPD rat models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…A recent study has elaborated the relation between inflammation and OA pain and prognosis, and that new appealing therapies targeting inflammation might contribute to satisfactory pain relief [47]. A large body of evidence has verified that activation of inflammatory factors, including IL1β, TNF-α, and IL-6 [48], is implicated in the development and progression of and OA [49,50], while the blockage of these proinflammatory cytokines serves as an appealing treatment option for OA [51]. Moreover, elevation of IL-1β can be observed in synovial fluid, subchondral bone, and cartilage tissues from OA patients [52].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has elaborated the relation between inflammation and OA pain and prognosis, and that new appealing therapies targeting inflammation might contribute to satisfactory pain relief [47]. A large body of evidence has verified that activation of inflammatory factors, including IL1β, TNF-α, and IL-6 [48], is implicated in the development and progression of and OA [49,50], while the blockage of these proinflammatory cytokines serves as an appealing treatment option for OA [51]. Moreover, elevation of IL-1β can be observed in synovial fluid, subchondral bone, and cartilage tissues from OA patients [52].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK, an intracellular Ser/Thr protein kinase, is involved in a variety of signaling pathways and plays an important role in cell cycle regulation [ 137 ]. Studies have reported that NAC can improve COPD-related pulmonary fibrosis by activating immune response and suppressing the EMT process through VWF/P38 MAPK signaling pathway in vivo and in vitro experiments [ 15 ]. In addition, TACE/TGF-α/EGFR signaling pathway is found activated in CSE-exposed human airway epithelial cells, and blocking the TACE/TGF-α/EGFR signaling pathway can inhibit the CSE-induced EMT process [ 138 ].…”
Section: Signalling Pathways Involved In Emt Induced By Cigarette Smo...mentioning
confidence: 99%
“…This suggested antioxidant N -acetylcysteine may contribute to EMT inhibition, thereby alleviating COPD pulmonary fibrosis. NAC could ameliorate COPD-induced pulmonary fibrosis by promoting immune response and inhibiting the EMT process via the VWF/p38 MAPK axis [ 15 ].…”
Section: Potential Therapies For Emt In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant and anti-inflammatory actions of NAC in diverse respiratory diseases have been proved [ 9 ]. NAC is associated with alleviation in symptoms and delay in exacerbations of chronic obstructive pulmonary disease [ 10 ]. In addition, NAC has been found to inhibit COVID-19 replication and virus-induced apoptosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%